Deformation Character of the Aluminum Alloy AA 6063 Depending on the Homogenization State - Kelesoglu, Erguen; Erarslan, Yaman; Ozer, Gokhan (WALTER DE GRUYTER GMBH, 2009)
In the work for this contribution, homogenization heat treatment was evaluated with respect to its effect on deformation ability of AA6063 aluminum alloy which is a widely used extrusion alloy. The samples machined from extrusion billets were homogenized at 540 degrees C, 560 degrees C and 580 degrees C for a time period of 2, 4, 6, 8 and 10 h. The homogenization state of the samples was assessed via microstructure examination. The hardness of the samples was determined using Brinell hardness method. Tensile test was carried out in order to evaluate the deformation ability. Tensile strength and elongation at rupture were compared depending on the homogenization state of the alloy. Depending on the homogenization grade, the elongation at rupture was increased, and samples showed a gradual shift from brittle fracture to ductile fracture.
Keywords: Materials Science